Pre-clinical evaluation of novel mucoadhesive bilayer patches for local delivery of clobetasol-17-propionate to the oral mucosa. (September 2018) - Colley, H.E.; Said, Z.; Santocildes-Romero, M.E.; Baker, S.R.; D'Apice, K.; Hansen, J.; Madsen, L. Siim; Thornhill, M.H.; Hatton, P.V.; Murdoch, C.
Abstract: Oral lichen planus (OLP) and recurrent aphthous stomatitis (RAS) are chronic inflammatory conditions often characterised by erosive and/or painful oral lesions that have a considerable impact on quality of life. Current treatment often necessitates the use of steroids in the form of mouthwashes, creams or ointments, but these are often ineffective due to inadequate drug contact times with the lesion. Here we evaluate the performance of novel mucoadhesive patches for targeted drug delivery. Electrospun polymeric mucoadhesive patches were produced and characterised for their physical properties and cytotoxicity before evaluation of residence time and acceptability in a human feasibility study. Clobetasol-17-propionate incorporated into the patches was released in a sustained manner in both tissue-engineered oral mucosa and ex vivo porcine mucosa. Clobetasol-17 propionate-loaded patches were further evaluated for residence time and drug release in an in vivo animal model and demonstrated prolonged adhesion and drug release at therapeutic-relevant doses and time points. These data show that electrospun patches are adherent to mucosal tissue without causing tissue damage, and can be successfully loaded with and release clinically active drugs. These patches hold great promise for the treatment of oral conditions such as OLP and RAS, and potentially many other oral lesions. Graphical abstract: